Cukai Dan Pajak Carbol (Carbon Bungkusan Belanja Online) Sebagai Ekstensifikasi Cukai Plastik Dan Pajak Carbon Untuk Mendukung Keberlanjutan Lingkungan - Alexander, Rio Fernando (Peneliti.net, 2025)
The rise of e-commerce transactions in Indonesia has led to a surge in plastic waste from online shopping packaging. Poorly managed plastic waste contributes to environmental degradation and accelerates climate change. To address this issue, fiscal policies are needed to internalize the negative externalities of plastic consumption. This study aims to examine the extensification of plastic excise and carbon tax on online shopping packaging (Carbol) as fiscal instruments to support environmental sustainability. One of the implementations of plastic packaging tax is the UK through Plastic Packaging Tax. The research employs a literature review approach, analyzing secondary data from various sources, including regulations, research reports, and case studies of similar policy implementations in other countries. The analysis reveals that the imposition of excise and Carbol tax can serve as instruments to regulate plastic consumption in e-commerce through push and pull factors. Carbol excise is targeted at sellers as a disincentive for using plastic packaging, while Carbol tax is applied to consumers as compensation for the carbon footprint generated from online shopping. A piggybacking tax scheme is proposed, with excise collection managed by the Directorate General of Customs and Excise (DJBC) and tax collection by local governments. The implementation of excise and Carbol tax has the potential to reduce plastic use in the e-commerce sector while increasing national and regional revenues. However, its success requires synergy between the government, e-commerce platforms, and society.